Kewenangan Kelurahan di Kota Surabaya dalam Menemukan Kepemilikan Hak Atas Tanah - Eko Susilo; Tahegga Primananda Alfath (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze and identify the authority of urban villages (Kelurahan) in Surabaya City in the context of determining land ownership rights and to examine the legal consequences arising from these policies or actions. This issue is crucial given the frequent ambiguity in the role of urban villages in the field in land administration. The research method used is a juridical-normative approach, analyzing laws and regulations, specifically Law Number 5 of 1960 concerning the Basic Agrarian Law (UUPA) and its derivative regulations, which are then linked to practical implementation in Surabaya City. The results indicate that, from a juridical-normative perspective, urban villages (Kelurahan) in Surabaya City do not have attributive or substantive authority to determine the legal status of land ownership rights. The exclusive authority to determine rights rests with the National Land Agency (BPN). However, in practice, urban villages (Kelurahan) play a significant role as verifiers of physical ownership and administrators of land history at the local level. This role is realized through the issuance of documents such as the Certificate of Physical Control of a Land Plot (Sporadik), which serves as initial evidence and an essential prerequisite for the initial land registration process at the BPN. Regarding legal consequences, the Village Head's actions are divided into two: first, the issuance of administrative documents (Sporadic) is valid as factual evidence, but does not have final legal force to declare ownership. Second, if the Village Head acts beyond his authority (ultra vires) by attempting to establish rights, then his legal product is null and void because it violates the principles of legality and the hierarchy of laws and regulations. The conclusion of this study emphasizes the need for a clear understanding of the limits of the Village Head's authority to ensure legal certainty and order in the land sector in Surabaya City.